Observations of the third instar larva and puparium of Chrysomya bezziana (Diptera: Calliphoridae) - Sukontason K.L. (2014)
Observations on the ultrastructure of the third instar larva and puparium of the Old World screw-worm fly, Chrysomya bezziana, are presented utilizing both light microscopy (LM) and scanning electron microscopy (SEM). Results of this study indicate that the shape of the intersegmental spines between the pro- and mesothorax markedly differ from other blow fly species (Chrysomya megacephala, Chrysomya rufifacies, Chrysomya nigripes, Lucilia cuprina) in being broad-based with sharp recurved tips. Other characters such as the posterior spiracles, number of papillae on the anterior spiracles, oral grooves, and posterior spiracular hairs also differ. The strong and robust mouthhooks may explain the ability of larvae to penetrate deeply into human tissues. Perforated sieve plates covered with antler-like projections were observed within the anterior spiracles of the puparium of C. bezziana. The posterior spiracular discs each bear three spiracular slits with ≈2-μm wide openings that were viewed either open or closed by a membrane underneath. This study expands our knowledge of the fine details of the external morphology of both the third instar larva and puparium of C. bezziana, which is an obligatory myiasis-producing species in many regions. A key to differentiate the third instar of C. bezziana from other blow flies in Thailand is given. © 2006 Springer-Verlag.